Impact of Carbon Peak Policy on the Valuation of Automobile Manufacturing Companies-- Take BYD Auto Manufacturing Company as an Example (Asian Business Research, 2022)
This article is intended to reach peak carbon policy as the breakthrough point, to adopt new energy automotiveindustry is an important part of the carbon amount to peak strategy this conclusion, and with the company as theresearch object, by adopting division of the valuation method and price-to-sales ratio valuation method toestimate the company eventually concluded that carbon reach peak policy analysis on the influence of theautomobile manufacturing company valuations and make relevant summary.